Identifying Patient Characteristics That Predict Drug‐Induced Sleep Endoscopy Anatomy. (25th January 2022) - Gao, Thomas Zhang; Pan, Xueliang; Naik, Akash; Khandalavala, Rohan; Ramsell, Stuart; Gibbs, Hannah; Chio, Eugene
Abstract : Objective: To examine if age, sex, body mass index (BMI), neck circumference, or apnea‐hypopnea index can predict whether a patient will demonstrate velopharyngeal complete circumferential (CC) collapse on drug‐induced sleep endoscopy (DISE). Study Design: Single‐center retrospective review at The Ohio State Wexner Medical Center of 289 patients between March 2014 and June 2020. Setting: Quaternary care hospital. Methods: Patient characteristic and DISE information was extracted from charts and summarized with mean and standard deviation for continuous variables and count and percentage for categorical. CC collapse and patient characteristic associations were explored: 2‐sample t test for continuous and chi‐square test for categorical. Classification and regression tree (CART) analysis with 3‐fold cross‐validation was employed to search for the best CC collapse predictors. Results: Male and female BMI and female neck circumference were correlated to velopharyngeal CC collapse, with BMI more strongly correlated. CART analysis for males showed that a BMI ≤34.8 kg/m 2 is associated with an 89.4% chance of not demonstrating velopharyngeal CC collapse vs 48% for BMI >34.8 (area under the curve [AUC] = 0.705; AUC >0.7 is acceptable). For females, the CART analysis showed that a BMI ≤36.4 is associated with a 98.4% of not demonstrating velopharyngeal CC collapse vs 30.8% for BMI >36.4 (AUC = 0.73). For females, a neck circumference ≤38.05 cm is associated with a 100% chance of not demonstrating velopharyngeal CC collapse vs 18.4% for >38.05 cm (AUC = 0.72). Conclusion: The BMI values for males and females and the female neck circumference values established by the CART model may accurately predict DISE anatomy and possible candidacy for hypoglossal nerve stimulation.